Żydowskie dewekut w postaci kontemplacji tetragramu oraz kombinatoryki literowej jako droga duchowego rozwoju - Brylla, Dorota (Poznańskie Studia Teologiczne, 2010)
The article deals with the Jewish concept of devekut („clinging on”), a type of communio mystica, realized in two kabbalistic - i.e. specific for mystical, esoteric trend in Judaism, originated in the 12th century - methods. These methods are the meditation and contemplation (moreover also: visualization, recitation and vocalization) of the divine biblical name YHWH - Tetragrammaton, and the explication of it, the so called science of the combination of letters, hochmah ha-tzeruf, immanently associated with the sacred text (precisely: the combinations and permutations made on it, namely on divine name/names), which most known representative was Abraham Abulafia. What distinguishes present text from other scientific publications about both Abulafia’s mystical technique and the concentration on Tetragrammaton, is the emphasis placed on the ideal of devekut, which can be implemented in these mystic behaviours, as well as treating the presented mystical methods as the way, simultaneously - the system, of personal spiritual growth, spiritual development and self-cultivation.